Education for Living Together in Diversity - Vižintin, Marijanca Ajša (Two Homelands, 2012)
This article introduces the basis for developing multicultural education in United States of America and intercultural education in Europe. Living together in changing and diverse communities represents a big challenge. Teachers working in schools and students learning in heterogeneous classes can solve this challenge only with an adequate public support, where each individual can develop his/her intercultural competence. A common terminology should be explored together with currently developed concepts and the experience already gained from multicultural and intercultural education. Although professional discussions about multicultural and intercultural education, intercultural competence and interculturality as a teaching concept have also been developed in Slovenia, the gap between a declarative level for multiculturality and the actual (teaching) practices is still considerably wide.